Differences in transcriptional activity of human papillomavirus type 6 molecular variants in recurrent respiratory papillomatosis - Bonfim, Caroline Measso do [UNESP]; Simão Sobrinho, João; Nogueira, Rodrigo Lacerda; Kupper, Daniel Salgado; Valera, Fabiana Cardoso Pereira; Nogueira, Maurício Lacerda; Villa, Luisa Lina; Rahal, Paula [UNESP]; Sichero, Laura (Public Library Science, 2015)
A significant proportion of recurrent respiratory papillomatosis (RRP) is caused by human papillomavirus type 6 (HPV-6). The long control region (LCR) contains cis-elements for regulation of transcription. Our aim was to characterize LCR HPV-6 variants in RRP cases, compare promoter activity of these isolates and search for cellular transcription factors (TFs) that could explain the differences observed. The complete LCR from 13 RRP was analyzed. Transcriptional activity of 5 variants was compared using luciferase assays. Differences in putative TFs binding sites among variants were revealed using the TRANSFAC database. Chromatin immunoprecipation (CHIP) and luciferase assays were used to evaluate TF binding and impact upon transcription, respectively. Juvenile-onset RRP cases harbored exclusively HPV-6vc related variants, whereas among adult-onset cases HPV-6a variants were more prevalent. The HPV-6vc reference was more transcriptionally active than the HPV-6a reference. Active FOXA1, ELF1 and GATA1 binding sites overlap variable nucleotide positions among isolates and influenced LCR activity. Furthermore, our results support a crucial role for ELF1 on transcriptional downregulation. We identified TFs implicated in the regulation of HPV-6 early gene expression. Many of these factors are mutated in cancer or are putative cancer biomarkers, and must be further studied.